A novel enhanced differential evolution algorithm for outbound logistics of the poultry industry in Thailand - Karn Moonsri; Kanchana Sethanan; Kongkidakhon Worasan (Journal of Open Innovation: Technology, Market, and Complexity, 2022)
Outbound logistics is a crucial field of logistics management. This study considers a planning distribution for the poultry industry in Thailand. The goal of the study is to minimize the transportation cost for the multi-depot vehicle-routing problem (MDVRP). A novel enhanced differential evolution algorithm (RI-DE) is developed based on a new re-initialization mutation formula and a local search function. A mixed-integer programming formulation is presented in order to measure the performance of a heuristic with GA, PSO, and DE for small-sized instances. For large-sized instances, RI-DE is compared to the traditional DE algorithm for solving the MDVRP using published benchmark instances. The results demonstrate that RI-DE obtained a near-optimal solution of 99.03% and outperformed the traditional DE algorithm with a 2.53% relative improvement, not only in terms of solution performance, but also in terms of computational time.
Keywords: 650; multi-depot vehicle routing problem; novel enhanced differential evolution algorithm; outbound logistics planning